2007
DOI: 10.4049/jimmunol.179.6.4212
|View full text |Cite
|
Sign up to set email alerts
|

CD45RB Ligation Inhibits Allergic Pulmonary Inflammation by Inducing CTLA4 Transcription

Abstract: CD45, a type I transmembrane protein tyrosine phosphatase expressed on nucleated hemopoietic cells, is prominently involved in T cell activation. Ligation of CD45RB isoforms has been associated with transplant tolerance. A recent genotyping analysis of asthma indicates a correlation with CD45 splicing. In this study, we administered an anti-CD45RB mAb (aCD45) in a murine model of allergic asthma and found that CD45RB ligation decreases allergic responses. aCD45 decreases allergen-induced pulmonary eosinophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…37,38 Blockade of CTLA-4 in animal models has been shown to maintain or increase allergic responses and inflammation, 39 with increased eosinophil numbers, IgE levels, and allergen-induced IL-13 levels, whereas increased CTLA-4 expression inhibits allergic pulmonary inflammation. 40 In addition, CTLA-4 can efficiently inhibit inflammatory responses in human subjects in vivo, as evidenced by the successful treatment of chronic inflammatory diseases by the CTLA-4-immunoglobulin fusion protein abatacept. 41,42 The 39-UTR of the CTLA-4 transcript contains an evolutionarily conserved miR-155 binding site, and we found that mutation of this site abolished miR-155-mediated suppression of CTLA-4, as demonstrated by luciferase reporter assays.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Blockade of CTLA-4 in animal models has been shown to maintain or increase allergic responses and inflammation, 39 with increased eosinophil numbers, IgE levels, and allergen-induced IL-13 levels, whereas increased CTLA-4 expression inhibits allergic pulmonary inflammation. 40 In addition, CTLA-4 can efficiently inhibit inflammatory responses in human subjects in vivo, as evidenced by the successful treatment of chronic inflammatory diseases by the CTLA-4-immunoglobulin fusion protein abatacept. 41,42 The 39-UTR of the CTLA-4 transcript contains an evolutionarily conserved miR-155 binding site, and we found that mutation of this site abolished miR-155-mediated suppression of CTLA-4, as demonstrated by luciferase reporter assays.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular mechanisms behind RB-associated correlations (and RO) would better facilitate the design of CD45-based therapeutic approaches against disease. Antibodies against RB have been shown to have both an immunosuppressive [37][38][39] and stimulatory 40,41 effect on lymphoid cell behavior depending on various environmental factors, including differential associations with multiple surface molecules. 42,43 Anti-RB treatment is useful as an immunotherapeutic agent and induces transplant tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jen and colleagues (31) demonstrated that blocking CD45RB with a CD45RB antagonist resulted in a substantial increase in airway inflammation. However, the administration of a CD45RB agonist caused a significant decrease in airway inflammation and a substantial increase of CTLA-4 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%